Digital technologies for oversize goods road transportation - O. Y. Smirnova; Yu. A. Ertman (Вестник СибАДИ, 2022)
Introduction. The scheduling a transportation route of overweight and oversize goods by road is necessary to perform taken into account road traffic safety and security of artificial engineering structures (bridges, railway crossing and others). The monitoring and control of these procedures are performed by a licensing system in Russia. During the delivery a driver must carry out the transportation of such cargo within the approved route that is specified in a particular paper (authorization) located in the vehicle. Issues appear mostly during first shipment organization and when the route is outside the permanent vehicles location, when road network and bypass schemes are not familiar for the driver and the current GPS-systems bases do not include formal designations of roads according to state register. The authors suppose digital technologies implementation has to facilitate easier abnormal load shipments violations-free sufficiently.The Materials and methods. A transportation organisation model of abnormal loads by BPMN notation has been developed. The key control points have been determined by the authors on the base of their own experience.The results. An information model of forming and transmitting to the carrier authorization to transport abnormal load within the approved route has been developed. In the authorization the link to the cartographic resource is inserted in one of the QR-code field. Such approach makes possible to identify approved route clearly and unambiguously.Uniqueness and practical meaning. The information model uniqueness consists of the transmission way of approves route to the customer – not the sequence of transit localities, but the cartographic resource. The practical implementation of such decision is addressed to help a carrier (a driver) to perform the abnormal load transportation strictly within the approved route.